Pathways to mesoporous resin/carbon thin films with alternating gyroid morphology - Zhang, Qi (2019)
Three-dimensional (3D) mesoporous thin films with sub-100 nm periodic lattices are of increasing interest as templates for a number of nanotechnology applications, yet are hard to achieve with conventional top-down fabrication methods. Block copolymer self-assembly derived mesoscale structures provide a toolbox for such 3D template formation. In this work, single (alternating) gyroidal and double gyroidal mesoporous thin-film structures are achieved via solvent vapor annealing assisted co-assembly of poly(isoprene-block-styrene-block-ethylene oxide) (PI-b-PS-b-PEO, ISO) and resorcinol/phenol formaldehyde resols. In particular, the alternating gyroid thin-film morphology is highly desirable for potential template backfilling processes as a result of the large pore volume fraction. In situ grazing-incidence small-angle X-ray scattering during solvent annealing is employed as a tool to elucidate and navigate the pathway complexity of the structure formation processes. The resulting network structures are resistant to high temperatures provided an inert atmosphere. The thin films have tunable hydrophilicity from pyrolysis at different temperatures, while pore sizes can be tailored by varying ISO molar mass. A transfer technique between substrates is demonstrated for alternating gyroidal mesoporous thin films, circumventing the need to re-optimize film formation protocols for different substrates. Increased conductivity after pyrolysis at high temperatures demonstrates that these gyroidal mesoporous resin/carbon thin films have potential as functional 3D templates for a number of nanomaterials applications.